GEOGRAPHICAL ASSESSMENTS ON THE RELATIONSHIPS BETWEEN AGRAIAN ECONOMY AND POPULATION AFTER 1990S (CASE STUDY IN ALBANIA) - Dhimitri, Jostina (European Scientific Journal, ESJ, 2013)
Western Lowland, being under the influence of a growing humanization, has been evolved all along the agricultural ecosystem. Physical environmental factors have played an important role in the structure,, composition and dynamics in general and in agricultural environment in particular. This ecosystem dynamics is associated with the evolution of agricultural space, agrarian relations and property statements. In terms of small land property it is characterized a private output with few investments and a competitive market. As one of the main economic sectors, the agricultural production provides a good part of its income in Lushnja district, as part of the Western Lowland. Due to the geographical position, its favorable climatic factors, soil quality, etc., in the district of Lushnja, grains, vegetables, fodder are cultivated mainly in the plains and the various cultures in greenhouses. While in hilly areas olives, vineyards and tobacco are being cultivated. It is distinguished for an agriculture potential, who has conditioned the living community in this district. Population by her presence has constantly exerted pressure on the working land space. This pressure is expressed through the calculation of the physiological density. Free movement of population after 1990s, established a good part of the population in the Western Lowland and Lushnja district (mainly coming from mountainous areas and eastern parts of Albania). The article aims at presenting a geographical assessment of case study area, certain aspects of the agricultural economy and relations with demographic developments in recent years